Society and Culture : introduction to sociology and anthropology - Panopio, Isabel S.; Rolda, Realidad Santico (Makati City, Philippines : Goodwill Book Store, 2000)
Sociology and anthropology involve the systematic study of social life and culture in order to understand the causes and consequences of human action.
CHAPTER 1. The study of sociology and anthropology -- 2. Prehistory of the Philippines -- 3. Society and culture -- 4. Philippine Values -- 5. Personality and socialization -- 6. Social-Cultural change -- 7. Social Organization -- 8. Gender: Concepts, Theories & Views -- 9. Social stratification -- 10. Ethnic Groups -- 11. Economic Organization -- 12. Political organization -- 13. Religion and society -- 14. Rural and Urban Community -- 15. Population dynamics and change.
Includes bibliographical references and index.
Keywords: SOCIOLOGY